2003
DOI: 10.1111/j.1752-7325.2003.tb03497.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Caries: Prevalence and Risk Factors in Seoul, Korea

Abstract: This study demonstrates that the prevalence of ECC was high among children in Seoul. Early educational intervention programs for pregnant women and mothers of young children should be developed based on the risk factors identified in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
33
2
11

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 18 publications
9
33
2
11
Order By: Relevance
“…No statistical significance was found in relation to this variable and the occurrence of severe childhood caries (p>0.05), which results are similar to other studies that also found no association [7,13]. However, some studies have found a statistically significant relationship between occurrence of severe childhood caries and low income level [15,22,24,28]. According to these authors, the higher the income level, the lower the incidence of severe childhood caries.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…No statistical significance was found in relation to this variable and the occurrence of severe childhood caries (p>0.05), which results are similar to other studies that also found no association [7,13]. However, some studies have found a statistically significant relationship between occurrence of severe childhood caries and low income level [15,22,24,28]. According to these authors, the higher the income level, the lower the incidence of severe childhood caries.…”
Section: Discussionsupporting
confidence: 76%
“…Although the increased use of nocturnal bottle, coupled with early weaning, is considered a predisposing factor for severe childhood caries, the findings of this research did not examine the association between bottle use and the occurrence of caries (p>0.05), since 70% of children who had caries did not have this habit. Reinforcing this finding, other studies [7,13,15], also found no significant association between daily frequency of use of bottle containing fermentable carbohydrates and the occurrence of severe childhood caries. Caries is a disease that can be prevented, provided there is early intervention and families at risk receive oral hygiene guidance [1][2][3][9][10][11][12].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations